Scanning tunneling microscopy and spectroscopy of tin oxide films - Castro, Miriam Susana (2001)
SnO2 thick films have been studied with scanning tunneling microscopy and spectroscopy. Topographic images revealed grains with an average diameter of about 100 nm and roughness of 50 nm. Tunneling current-voltage characteristics measured indicate that these small grains present a non rectifying behavior. Temperature dependence of electrical conductivity during heating and cooling and resistivity transients at step isothermal changes in oxygen pressure were also investigated. Results are consistent with those of STM and confirm that oxygen adsorption and diffusion into the tin oxide grain account for the observed conductance changes.